Deuterium MAS NMR Studies of Dynamics on Multiple Timescales: Histidine and Oxalic Acid1. Issue 1 (30th October 2014) - Chan‐Huot, Monique; Wimperis, Stephen; Gervais, Christel; Bodenhausen, Geoffrey; Duma, Luminita
Abstract Deuterium (2H) magic‐angle spinning (MAS) nuclear magnetic resonance is applied to monitor the dynamics of the exchanging labile deuterons of polycrystalline L‐histidine hydrochloride monohydrate‐d7 and α‐oxalic acid dihydrate‐d6. Direct experimental evidence of fast dynamics is obtained from T1Z and T1Q measurements. Further motional information is extracted from two‐dimensional single‐quantum (SQ) and double‐quantum (DQ) MAS spectra. Differences between the SQ and DQ linewidths clearly indicate the presence of motions on intermediate timescales for the carboxylic moiety and the D2O in α‐oxalic acid dihydrate, and for the amine group and the D2O in L‐histidine hydrochloride monohydrate. Comparison of the relaxation rate constants of Zeeman and quadrupolar order with the relaxation rate constants of the DQ coherences suggests the co‐existence of fast and slow motional processes.